Characterization of aerosol composition, concentrations, and sources at Baengnyeong Island, Korea using an aerosol mass spectrometer. (November 2015) - Lee, Taehyoung; Choi, Jinsoo; Lee, Gangwoong; Ahn, Junyoung; Park, Jin Soo; Atwood, Samuel A.; Schurman, Misha; Choi, Yongjoo; Chung, Yoomi; Collett, Jeffrey L.
Abstract: To improve understanding of the sources and chemical properties of particulate pollutants on the western side of the Korean Peninsula, an Aerodyne High Resolution Time of Flight Aerosol Mass Spectrometer (HR-ToF-AMS) measured non-refractory fine (PM1 ) particles from May to November, 2011 at Baengnyeong Island, South Korea. Organic matter and sulfate were generally the most abundant species and exhibited maximum concentrations of 36 μg/m 3 and 39 μg/m 3, respectively. Nitrate concentrations peaked at 32 μg/m 3 but were typically much lower than sulfate and organic matter concentrations. May, September, October, and November featured the highest monthly average concentrations, with lower concentrations typically observed from June through August. Potential source contribution function (PSCF) analysis and individual case studies revealed that transport from eastern China, an area with high SO2 emissions, was associated with high particulate sulfate concentrations at the measurement site. Observed sulfate aerosol sometimes was fully neutralized by ammonium but often was acidic; the average ammonium to sulfate molar ratio was 1.49. Measured species size distributions revealed a range of sulfate particle size distributions with modes between 100 and 600 nm. Organic aerosol source regions were widespread, including contributions from eastern China and South Korea. Positive matrix factorization (PMF) analysis indicated three "factors, " or types of organic aerosol, comprising one primary, hydrocarbon-like organic aerosol (HOA) and two oxidized organic aerosol (OOA) components, including a more oxidized (MO-OOA) and a less oxidized (LO-OOA) oxidized organic aerosol. On average, HOA and OOA contributed 21% and 79% of the organic mass (OM), respectively, with the MO-OOA fraction nearly three times as abundant as the LO-OOA fraction. Biomass burning contributions to observed OM were low during the late spring/early summer agricultural burning season in eastern China, since airflow into eastern China during the Asian Monsoon generally prevents transport of emissions eastward to the Korean Peninsula. Concentrations of the m/z 60 AMS biomass burning marker were more abundant in autumn, when transport patterns appeared to bring some smoke from fires in northern Asia to the island. Highlights: We measured the overall chemical properties of particulate matter at Baengnyeong Island, Korea. Organic matter and sulfate were the dominant chemical species in PM1. Observed organic aerosol was generally highly oxidized. Significant increases in sulfate concentration by transport from eastern China. Organic aerosol transported from both China and other regions of east Asia.